1997
DOI: 10.1002/(sici)1097-0274(199709)32:3<283::aid-ajim15>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Paternal occupational exposure around conception and spina bifida in offspring

Abstract: A multi-center case-referent study was conducted on the relation between paternal occupa tional exposure and spina bifida in offspring. Cases were born between 1980 and 1992 in The Netherlands. Referents were recruited from hospitals and from, the general population. Postal questionnaires were used to gather information on occupation and potential confounders. Through job-specific telephone interviews with 122 case fathers and 411 referent fathers, detailed exposure information was collected on specific tasks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Significantly reduced ORs were apparent for paternal occupational exposure to inhaled hydrocarbons and metal‐working oil mists. The findings for agrochemicals and animals overlap and have been seen before 3–6,10–12 . The apparent protective effect of fathers working in specific occupations has not been previously described.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Significantly reduced ORs were apparent for paternal occupational exposure to inhaled hydrocarbons and metal‐working oil mists. The findings for agrochemicals and animals overlap and have been seen before 3–6,10–12 . The apparent protective effect of fathers working in specific occupations has not been previously described.…”
Section: Discussionmentioning
confidence: 52%
“…The findings for agrochemicals and animals overlap and have been seen before. [3][4][5][6][10][11][12] The apparent protective effect of fathers working in specific occupations has not been previously described. Clearly, a range of explanations may account for these apparent effects.…”
Section: Discussionmentioning
confidence: 96%
“…The relation between paternal occupational exposure shortly before pregnancy and risk of spina bifida in offspring was studied by Blatter et al 30 A total of 470 live born children with spina bifida aperta (as defined by the ninth revision of the international classification of diseases (ICD-9)) was identified by review of hospitals' medical records in The Netherlands. No associations were identified for other paternal occupational exposures, such as organic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Higher levels of the OPs diazinon (maximum = 160 ppm), chlorpyrifos (maximum = 33 ppm), and malathion (maximum = 1.6 ppm) were found in house dust in farmworker homes (6 (52)(53)(54)(55). Other studies have reported that parental exposure to pesticides or application of pesticides in the home is associated with certain birth defects including neural tube and other birth defects (56,57).…”
mentioning
confidence: 99%